PROGRAMME DESCRIPTION: Using real-world cases, innovation and rhetorical tools to teach social pharmacy - Nørgaard, Lotte Stig; Møllebæk, Mathias; Halstrøm , Per Liljenberg; Riis , Nina Louise Fynbo; Christensen, Vibeke Brix; Arevalo, Lourdes Cantarero (Pharmacy Education, 2021)
Background: Innovation refers to the process in which individuals or organisations transform ideas into novel products, services or processes. Pharmacy graduates are increasingly expected to have the competencies necessary to find innovative solutions to medicine-related challenges, particularly solutions addressing patient´s need and societal aspects of medicine use. Objective: To describe and discusses the rationale, development, implementation and evaluation of the pharmacy course ‘Contemporary Social Pharmacy’ (CONSOC), and to summarise lessons learned. Methods: Several methods and models were used to develop, run and evaluate the course. The course examination consisted of a written report and an oral presentation and defence of the report. The course was evaluated through a student assessment questionnaire and oral and written feedback from case providers and the teachers. Results: Three selected case reports representing particularly innovative solutions are described. The student evaluations revealed that nine out of 14 course learning objectives were either fully or partly fulfilled, and that what students liked best from the course were the teamwork, the open discussions, the real-world cases and the innovation features. The teachers and case providers also found the course rewarding and extremely positive. Conclusion: Teaching innovation opens up new possibilities for educators and researchers. The CONSOC course introduced several novel components, but the increased complexity of the course also presented challenges to students and faculty alike.